Fracture behavior of graphene mounted on stretchable substrate. (November 2016) - Niu, Tianxiao; Cao, Guoxin; Xiong, Chunyang
Abstract: The fracture behavior of graphene monolayer with the substrate binding effect can be investigated by the indentation response of graphene/poly-dimethylsiloxane (PDMS) nanocomposite (graphene monolayer mounted on super-soft substrate-PDMS) performed by atomic force microscopy (AFM). The nonlinear elastic constant of graphene is predicted by the reverse analysis of the experimental results using finite element method (FEM), based on which the intrinsic strength of graphene monolayer is evaluated as 37.6 N/m (corresponding to 112 GPa) and the corresponding strain is ∼0.23. It is found that the fracture stress of graphene is essentially not sensitive to the substrate binding effect (∼10% lower than their free-standing counterpart). On the basis of FEM, the deformation of graphene in graphene/PDMS under indentation is very similar to that of graphene in free-standing indentation, and the main strain of graphene is not transferred by the graphene/substrate interface but directly applied by the indentation load, which creates a very low deformation mismatch across the interface (or a very low interface stress). Therefore, there is no sliding/debonding occurrence for the graphene/PDMS interface in the indentation tests till the failure of graphene. The present work actually provides an alternative way to measure the fracture behavior of graphene with substrate sticking effect.